COL5A2 Inhibits the TGF-β and Wnt/β-Catenin Signaling Pathways to Inhibit the Invasion and Metastasis of Osteosarcoma - Han, Yan-Long; Luo, Dan; Habaxi, Kakeng; Tayierjiang, Julaiti; Zhao, Wei; Wang, Wei; Aikebaier, Wumaierjiang; Wang, Li (Frontiers in Oncology, 2022)
Osteosarcoma is the most common skeletal malignancy and is the second leading cause of cancer death in adolescents. Its highly aggressive nature and high propensity to metastasize lead to an extremely poor prognosis for patients with osteosarcoma. Therefore, finding a suitable treatment has become a matter of urgency. In this study, we first divided the samples into metastatic and non-metastatic groups using the Target database and obtained 1136 differentially expressed genes (DEGs) using differential analysis. A PPI network was constructed to analyze the network of action relationships among DEGs, and the top 10 genes were derived using the MCC algorithm in Cytoscape software. A risk scoring system for 10 key genes was constructed using the LASSO-COX prognostic risk model, and genes associated with osteosarcoma prognosis were screened based on multifactorial COX. COL5A2 gene was highly expressed in metastatic osteosarcoma and led to a poor prognosis. Furthermore, qRT-PCR and immunofluorescence assays confirmed the high expression of COL5A2 in human osteosarcoma cells. CCK-8 assay and scratch WB was used to determine whether the downregulation of COL5A2 expression inhibits the TGF-β signaling and Wnt/β-Catenin signaling pathways. In this study, we screened COL5A2 for prognostic relevance to osteosarcoma through bioinformatics analysis and demonstrated that COL5A2 inhibited osteosarcoma invasion and metastasis by suppressing the TGF-β signaling and Wnt/β-Catenin signaling pathways.